2018
DOI: 10.1507/endocrj.ej17-0017
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y promotes adipogenic differentiation in primary cultured human adipose-derived stem cells

Abstract: Abstract. Neuropeptide Y (NPY) is an important neurotransmitter in the control of energy metabolism. Several studies have shown that obesity is associated with increased levels of NPY in the hypothalamus. We hypothesized that the release of NPY has coordinated and integrated effects on energy metabolism in different tissues, such as adipocyte tissue, resulting in increased energy storage and decreased energy expenditure. Whether NPY has role in the molecular mechanism of human adipocyte tissue remains unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The NPY is reported to possess bimodal features. Accordingly, its biological action has been described not only in a concentration-dependent fashion [ 51 ], but also associated to the relative affinity with its receptors in the microenvironment [ 52 , 53 ]. The NPY-enhanced endocytosis result is in line with the increased expression of the endocytic receptor CD206 observed in NPY-stimulated macrophages, thus indicating the activation toward an M2-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The NPY is reported to possess bimodal features. Accordingly, its biological action has been described not only in a concentration-dependent fashion [ 51 ], but also associated to the relative affinity with its receptors in the microenvironment [ 52 , 53 ]. The NPY-enhanced endocytosis result is in line with the increased expression of the endocytic receptor CD206 observed in NPY-stimulated macrophages, thus indicating the activation toward an M2-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The NPY is reported to possess bimodal features. Accordingly, its biological action has been described not only in a concentration-dependent fashion 51 but also associated to the relative affinity with its receptors in the microenvironment 17 , 34 . Higher concentrations of NPY have been reported to neither increase cell proliferation, nor adipocytes differentiation and migration in wound scratch in vitro assays 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, there are few studies on NPY and adipose-derived stem cells (ADSCs), but it has still been shown that Y2R and Y5R are expressed in human ADSCs, and NPY may play a role in human ADSC proliferation and adipogenic differentiation by interacting with these two receptors [ 138 ]. Liu et al established a model of human ADSCs from human adipose tissue and differentiated them into adipocytes at different concentrations of NPY to determine the effects of different NPY doses on proliferation and adipogenic differentiation [ 138 ]. In their study, low-dose NPY treatment promoted the proliferation of human ADSCs, while high-dose treatment inhibited it.…”
Section: Applications Of Npy In Diseasesmentioning
confidence: 99%
“…In their study, low-dose NPY treatment promoted the proliferation of human ADSCs, while high-dose treatment inhibited it. NPY significantly promoted lipid accumulation, increased the size of lipid droplets, and increased the levels of adipocyte markers PPAR-γ and C/EBPα [ 138 ]. In conclusion, the prospective applications of NPY treatment of stem cells are promising.…”
Section: Applications Of Npy In Diseasesmentioning
confidence: 99%